Development of catalytic-converter system for motorcycle engine by using cobalt based titatium dioxide / Ku Halim Ku Hamid and Mohibah Musa - Ku Hamid, Ku Halim; Musa, Mohibah (2002)
Motorcycle emits substantial quantities of hydrocarbons (HC), carbon monoxide (CO), nitrogen oxide (NOx) and particulate matter. The emission could contribute to a poorer quality of air due to the increasing of motorcycle number. A catalytic exhaust control can be developed as an excellent solution for the problem and it is recognized to be the most cost-effective way to meet stringent emission standards. The three-way catalytic converters (TWC) were developed for 4-stroke engine is to oxidize the unburned HC and CO to form H20 and CO2 respectively as well as to reduce NOx to nitrogen. Two designs of catalytic converter were developed to compare the effectiveness combination of Co-TiO2 catalyst. The first design is an arrangement of wire mesh to replace the conventional honeycomb structure. While the second design in spiral shaped,' purposely to change the linear flow of the exhaust gases to a vortex flow. It was found that the technology developed with cost-effective concept successfully reduce the emission level of the toxic gases.